Lost in space? Searching for directions in the spatial modelling of individuals, populations and species ranges - Luca Borger (Biology Letters, 2010)
The workshop “Spatial models in ecology, management and conservation” held at Silwood Park (UK), 9-11 March 2010, aimed to synthesize recent progress in modelling the spatial dynamics of individuals, populations and species ranges and to provide directions for research. It brought together marine and terrestrial researchers working on spatial models at different levels of organisation, and using empirical as well as theory-driven approaches. Different approaches, temporal and spatial scales, and practical constraints predominate at different levels of organisation and in different environments. However, there are theoretical concepts and specific methods that can fruitfully be transferred across levels and systems, including: habitat suitability characterisation, movement rules, and ways of estimating uncertainty.